Dysregulation of Lipid Metabolism in Macrophages Is Responsible for Severe Endotoxin Tolerance in FcgRIIB-Deficient Lupus Mice - Jaroonwitchawan, Thiranut; Visitchanakun, Peerapat; Dang, Phi Cong; Ritprajak, Patcharee; Palaga, Tanapat; Leelahavanichkul, Asada (Frontiers in Immunology, 2020)
The defect in FcgRIIB is commonly found in patients with lupus, especially in Asia. Because i) the extreme LPS-tolerance enhances sepsis-susceptibility in FcgRIIB-/- lupus mice and ii) LPS-tolerant macrophages demonstrates cellular energy depletion, then lipid might be an important alternative source for cell energy in LPS-tolerance and is explored. Hence, LPS-tolerance was induced by twice LPS administration in macrophages and in mice. Accordingly, LPS-tolerant FcgRIIB-/- macrophages demonstrated the lesser mitochondrial DNA (mtDNA) with the more severe ATP depletion together with the lower cytokine production in comparison with LPS-tolerant WT cells. With the lower energy status of LPS-tolerance in FcgRIIB-/- macrophages compared with WT, there was the more prominent accumulation of intracellular lipid droplets by oil red O staining with the higher phosphatidylethanolamine (PE) phospholipid in composition as determined by mass-spectrometry-based lipidomic analysis. In parallel, the expression of phosphatidylethanolamine N-methyltransferase (pemt), an enzyme responsible for PE metabolism, was lower and the abundance of phosphorylated AMP-activated protein kinase (AMPK-p), a molecule of ATP-restoration process, was higher in LPS-tolerant FcgRIIB-/- macrophages compared with WT. Interestingly, the induction of the proper intracellular lipid component attenuated LPS tolerance as compound C, an AMPK inhibitor, attenuated LPS-tolerance either in FcgRIIB-/- macrophages or in FcgRIIB-/- mice. Taken together, the intensely decreased cytokine production after 2nd LPS stimulation (LPS-tolerance) in FcgRIIB-/- macrophages was possibly due to the impact of an immense cytokine synthesis from the 1st dose of LPS including; i) the using-up of PEMT, an enzyme of the phospholipid synthesis pathway during the cytokine production, and ii) the induction of AMPK in response against the profound ATP-depletion. Hence, the manipulation of AMPK/PEMT axis provides a novel therapeutic candidate for treatment of severe LPS-tolerance in lupus.